Public Legal Awareness and the Effectiveness of Indonesia’s Personal Data Protection Law: Bridging Normative Framework and Privacy Paradox - Darnela, Lindra; Rusdiana, Erma (UIN Sunan Kalijaga Yogyakarta, 2025)
The increasing frequency of personal data breaches in Indonesia underscores the urgency of ensuring effective legal protection for citizens' privacy rights. The enactment of the Personal Data Protection Law (Law No. 27/2022) is a significant milestone, but its effectiveness depends not only on regulatory provisions but also on public legal awareness. Previous studies have largely focused on the normative framework and technical protections, with limited attention to how the public perceives and responds to personal data protection. This study applies a normative-empirical approach, combining doctrinal legal analysis with survey data, to assess the level of public legal awareness regarding data protection obligations and risks. The study's findings reveal that although many respondents acknowledge the potential dangers of excessive data disclosure, they still grant access to applications, reflecting the so-called privacy paradox. This inconsistency suggests that legal protection alone cannot guarantee effective law enforcement without parallel improvements in digital literacy and legal awareness. The novelty of this study lies in the linkage of Indonesian data protection law to the sociological dimensions of public legal awareness, a perspective rarely emphasized in previous research. The results contribute to academic discourse by integrating normative analysis with empirical evidence and offer practical implications for policymakers to design targeted legal education and digital literacy programs that strengthen the enforcement of the Personal Data Protection Law in Indonesia in particular and become a reflection and reference for other countries globally.